PENGARUH JANGKA WAKTU DAN PROSEDUR KREDIT TERHADAP KEPUTUSAN PENGAMBILAN KREDIT PADA PT BFI FINANCE INDONESIA GRESIK - syafii, mochamad - (GEMA EKONOMI, 2020)
This study aims to examine and examine the effect of credit period and credit procedures on credit decision making. This research takes place at PT BFI Finance Indonesia Gresik.This research is descriptive statistics using a quantitative approach. The method of data analysis with multiple linear regression, which includes the correlation coefficient, coefficient of determination, and t test and F test. The number of samples taken is 89 respondents and data collection is done by questionnaire that has been tested for validity and reliability.The results of the study show that the credit period has a positive and significant effect on credit decision making, which is indicated by the results of t count 2.867> t table 1.66256 and the value of t sign. 0.005 <? = 0.05. And credit procedures have a negative and insignificant effect on credit decision making, indicated by the results of t count 1.389 <t table 1.66256 and the value of t sign. 0.168> ? = 0.05. While simultaneously credit terms and credit procedures have a positive and significant effect on credit decision making, indicated by the calculated F value of 23.491> 3.95 F table and sign value. 0,000 <0,05.